Representations of Slovenian identity and analysis of the national(istic) discourse in the Slovenian magazine Kaplje - Šabec, Ksenija (Družboslovne razprave, 2019)
In the last decade, mediatisation has established itself as a key approach in media and communication studies. Its goal is to explain the vast transformations in social relations due to the increasing power of the media. I provide a theoretical and empirical critique of the institutionalist (strong) approach to mediatisation. Empirically, the article is based on semi-structured interviews with representatives of Slovenian political parties. As is noted, the main problem of mediatisation is that it perceives the power of the media abstractly. Even though holism is advocated, authors narrowly focus on the media, without embedding it in the social totality. For a critique of the ontological, epistemological and theoretical failures, I build the article on media sociology and the political economy of communication.
Keywords: Analiza diskurza; Discourse analysis; Nacionalizem; Narodna identiteta; National identity; Nationalism; Slovenian periodicals; Slovenska periodika